From democracy to managerialism: foundation universities as the embodiment of Finnish university policies - Poutanen, Mikko; Tomperi, Tuukka; Kuusela, Hanna; Kaleva, Veera; Tervasmäki, Tuomas (Journal of education policy, 2022)
The administrative systems of universities attest to a shift towards more managerial forms of leadership. This article outlines how strategic management was introduced in Finland in the 2000s and how this led to a significant de-democratisation of the university organisations, despite academic communities' resistance and explicit preference for democratic self-governance. The article illustrates how strategic management informed the reconceptualization of Finnish higher education in legislation (nationally), to de-democratise and to structurally reform the HE field, and in practice (locally), to drive through desired administrative reconfigurations. This anti-democratic transformation is embodied in a new institutional model: foundation universities, which have been presented as the flagships of Finnish higher education policy, are also vehicles of de-democratisation.